Strategic Development of Productive Waqf in Aceh: An ANP Approach - Nur, Mukhlish Muhammad; Ramadhan, Muhammad; Nasution, Yenni Samri Juliati (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
Waqf, as an Islamic philanthropic instrument, has significant potential for socio-economic development. However, realizing this potential requires effective management and strategic development, particularly in regions like Aceh where waqf assets are abundant. This study aims to identify the priority issues hindering the development of productive waqf in Aceh Province and propose solutions and strategies for its advancement. Employing a qualitative method, the research involved in-depth interviews with waqf experts and practitioners and the use of questionnaires. Data analysis was conducted using the Analytic Network Process (ANP) approach with Super Decision software. Findings reveal critical challenges related to waqif (endower) awareness, nazhir (trustee) professionalism, waqf asset allocation, legal documentation, and regulatory coordination. Key solutions include enhancing waqf literacy, strengthening nazhir capacity, optimizing asset utilization for economic value, improving waqf registration, and fostering synergy among stakeholders. The study recommends maximizing the role of Baitul Mal Aceh in implementing these strategies to unlock the full potential of productive waqf for the region's socio-economic growth.======================================================================================================== ABSTRAK - Strategi Pengembangan Wakaf Produktif di Aceh: Suatu Pendekatan ANP. Wakaf merupakan instrumen filantropi Islam yang memiliki potensi signifikan untuk pembangunan sosial-ekonomi. Namun, untuk mewujudkan potensi ini diperlukan manajemen dan strategi pengembangan yang efektif, terutama untuk daerah-daerah yang aset wakafnya melimpah, seperti Provinsi Aceh. Penelitian ini bertujuan untuk mengidentifikasi masalah-masalah utama yang menghambat pengembangan wakaf produktif di Aceh, dan memberikan solusi serta strategi pengembangannya. Dengan menggunakan metode kualitatif, data penelitian dikumpulkan melalui wawancara mendalam dengan para pakar dan praktisi wakaf serta penggunaan kuesioner. Analisis data dilakukan dengan pendekatan Analytic Network Process (ANP) menggunakan software Super Decision. Kajian menemukan adanya tantangan kritis terkait dengan kesadaran wakif, profesionalisme nazhir, alokasi aset wakaf, dokumentasi hukum, dan koordinasi regulasi. Solusi utama yang ditawarkan meliputi peningkatan literasi wakaf kepada masyarakat, penguatan kapasitas nazhir, optimalisasi pemanfaatan aset wakaf agar lebih bernilai ekonomis, peningkatan registrasi wakaf, dan mendorong sinergi di antara para pemangku kepentingan. Studi ini merekomendasikan untuk memaksimalkan peran Baitul Mal Aceh dalam menerapkan strategi ini sehingga seluruh potensi wakaf produktif di Aceh dapat dioptimalkan bagi pertumbuhan sosial-ekonomi daerah.